APPLICATION OF KING’s PHILOSOPHY TO EMPOWER COMMUNITY WELL-BEING - Nilkote, Reongwit; Charoenlak , Nipawan; Rueangsri, Wongsiri; Sukpom, Thitiwas (Journal of Social Science and Cultural, 2021)
The objectives of the research article were to 1) study the context and community well-being situation of case studies from 4 regions of Thailand, and 2) study the application of King’s philosophy to empower community well-being. This was qualitative research that studies data from documents, in-depth interviews, group discussions, participant observations. The key informants were community leaders who played a role in promoting community well-being, selected purposive sampling from representatives of model communities from representatives of 4 regions, namely 1) Northern region, 2) Northeastern region, 3) Central region, and 4) Southern region, 10 persons from each region, totaling 40 persons. By content analysis data, extracting lessons, and summarized overall. The study was found that: 1) the context and community well-being situation of case studies from 4 regions of Thailand include 1) The model community has social and cultural costs, have history, have tradition and culture that is a pattern of life as an identity, have lifestyle that is in harmony with the society and culture of each community, have community management in the form of "houses, temples, schools" as guidelines for community development leading to good community well-being, 2) population, occupation and income, most of them have income from agriculture. and general contracting, and 3) leadership groups and social relationships. Leaders play a role in driving promotion community well-being and can coordinate cooperation both within and outside the community. And 2) The application of King’s philosophy to empower community well-being has 4 level of application such as 1) understanding, 2) accessing, 3) developing and 4) upgrading by the main goal was coexistence of kinship society and the happiness of the community, and created the most complete self-reliant balance path.